[tex]a) |x - 1| = 3[/tex]
[tex]1)x - 1 = 3[/tex]
[tex]x = 3 + 1[/tex]
[tex]x = 4[/tex]
[tex]2) - x + 1 = 3[/tex]
[tex] - x = 3 - 1[/tex]
[tex] - x = 2 \: | \times ( - 1)[/tex]
[tex]x = - 2[/tex]
[tex]b) |x - 3| = 7[/tex]
[tex]1)x - 3 = 7[/tex]
[tex]x = 7 + 3[/tex]
[tex]x = 10[/tex]
[tex]2) - x + 3 = 7[/tex]
[tex] - x = 7 - 3[/tex]
[tex] - x = 4 \: | \times ( - 1)[/tex]
[tex]x = - 4[/tex]
[tex]3)2 |x - 3| - 13 = 25[/tex]
[tex]2 |x - 3| = 25 + 13[/tex]
[tex]2 |x - 3| = 38 \: | \div 2[/tex]
[tex] |x - 3| = 19[/tex]
[tex]1)x - 3 = 19[/tex]
[tex]x = 19 + 3[/tex]
[tex]x = 22[/tex]
[tex]2) - x + 3 = 19[/tex]
[tex] - x = 19 - 3[/tex]
[tex] - x = 16 \: | \times ( - 1)[/tex]
[tex]x = - 16[/tex]